Pengaruh Kepemimpinan Transformasional dan Green Human Resource Management terhadap Turnover Intention Dimediasi Organization Citizenship Behavior pada PT. Sango Indonesia - Rahma Amalia; Retno Purwani Setyaningrum (Jurnal Ilmiah Wahana Pendidikan, 2023)
Turnover intention is usually referred to as a form of expression that describes a person's situation or feelings towards a decision to leave a company or job. turnover intention can be avoided by a company because it is very detrimental to the company. the purpose of this study was to determine the effect of leadership transformation and green human resource management on turnover intention with organization citizen behavior as a mediating variable. This study used a quantitative method with a total sample of 45 employees of PT. This research was processed using SmartPLS data processing software and data collection was carried out using the Google formula. This research results that there is no significant effect between transformational leadership on turnover intention at PT.Sango Indonesia, there is no significant effect between green human resource management on turnover intention at PT.Sango Indonesia, there is no significant effect between organization citizen behavior on turnover intention, there is a positive and significant influence between transformational leadership on organizational citizen behavior. There is no positive and significant influence between transformational leadership on turnover intention which is mediated by organization citizen behavior at PT.Sango Indonesia.